Mary, Mary - McBain, Ed (New York : Warner Books, 1992)
Florida criminal attorney Matthew Hope never takes a case unless he is personally convinced of the innocence of the client. And retired schoolteacher Mary Barton--known to her neighbors as Mary, Mary, quite contrary--isn't the easiest of women to believe in. McBain's fabulously popular Matthew Hope series takes another twisted turn into hideous mutilation and murder.
70647
Keywords: Hope, Matthew (Fictitious character) -- Fiction; Trials (Murder) -- Fiction. -- Florida; Detective and mystery stories; Legal stories